Resource flows and the decomposition of regional inequality in Beijing-Tianjin-Hebei Metropolitan Region, 1990-2004 - Yuheng Li (European Regional Science Association (ERSA), 2011)
Urban-rural interaction in China has evolved a lot due to the economic growth and policy influences in the post-reform era since 1978. This evolution has exerted influences on the urban and rural areas in various aspects of demography, economy and environment. At present, China is on a track of fast economic growth and urbanization development which will definitely shape urban and rural areas at the same time. How will urban-rural interaction in China develop in the future? What are the implications for regional planning? The paper historically reviews and quantitatively assesses urban-rural interaction in China. It finds that urban-rural interaction has increased continuously in the post-reform era. The assessment of this interaction bears some resemblances to the historical evolution. The findings also reveal that the change of urban-rural interaction at the provincial level presents much regional difference in the period of 1980-2010. Besides, regional agglomeration of provinces of same level of urban-rural interaction has also emerged in China. The paper concludes through emphasizing the increase of urban-rural interaction in inland areas so as to decrease the regional inequality in China.
Keywords: 330